Metal monatomic doped MoS2 composite material as well as preparation method and application thereof

Through the preparation of metal single-atom doped MoS2 composite materials, the problem of insufficient photocatalytic activity of existing MoS2 is solved, and the effect of efficient NO reduction to NH3 at low voltage is achieved, showing its application potential in the field of photocatalytics.

CN119121298APending Publication Date: 2024-12-13SHANGHAI NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410727175.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-06
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing MoS2 photoelectrocatalytic materials have high overpotential during NO reduction, which limits their catalytic activity and makes it difficult to effectively convert high concentrations of NOx pollutants in the atmosphere.

Method used

Using metal single atom doped MoS2 composite materials, metal single atom doped MoS2 composite materials are prepared by using metal nanowires as templates, and high-voltage microwave reaction method to form a rod-like structure, which improves its catalytic activity and specific surface area, and is used for photoelectro-catalysis. Reduce NO to synthesize ammonia.

Benefits of technology

It realizes high-efficiency photoelectrocatalytic reduction of NO to NH3 at lower voltages, significantly improving catalytic activity and yield, and the preparation process is energy-saving and environmentally friendly, with large-scale application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121298A_ABST
    Figure CN119121298A_ABST
Patent Text Reader

Abstract

The invention relates to a metal monatomic doped MoS2 composite material and a preparation method and application thereof, the preparation method comprises the following steps: dispersing metal nanowires in water, then adding molybdenum salt and thiourea, and uniformly dispersing to obtain a precursor solution; and carrying out high-pressure microwave reaction on the precursor solution, and dissolving the metal nanowires to obtain the metal monatomic doped MoS2 composite material. The composite material comprises molybdenum disulfide nanorods grown according to a metal nanowire template, and metal single atoms uniformly dispersed on the surface of molybdenum disulfide after metal nanowires are dissolved. Compared with the prior art, the preparation method has the advantages of simplicity in preparation, high efficiency, energy conservation and the like, and the prepared composite material shows relatively high catalytic activity in photoelectrocatalytic NO reduction synthesis of ammonia.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of photoelectrocatalysis technology, and in particular relates to a metal single atom / MoS 2 Composite materials and their preparation methods and applications. Background Art

[0002] With the increasing development of human society, the ecological and environmental problems caused by more frequent human life and production activities have always attracted the attention of people from all walks of life around the world. Countries around the world are also introducing new policies and regulations to deal with the problem of pollutant emissions that are gradually threatening human survival.

[0003] Among them, nitrogen oxides (Nitrogen Oxides, NO x ) includes a series of compounds, such as NO (in NO X More than 90% of the total), NO 2 、N 2 O, etc. Most nitrogen oxides in urban atmosphere come from the combustion of fuels, and for cars fueled by gasoline and diesel, the concentration of nitrogen oxides in exhaust gas is quite high. x All of them have varying degrees of toxicity and pose a great threat to the environment, so there is an urgent need to develop methods for treating and converting nitrogen oxides.

[0004] In the context of the increasing demand for clean energy and sustainable development in today's society, photoelectrocatalytic technology has attracted much attention as a green and environmentally friendly energy conversion method. Photoelectrocatalytic technology uses light energy to stimulate the charge transfer process and promote the chemical reaction. It is widely used in the fields of water decomposition and carbon dioxide reduction. Using photoelectrocatalytic reduction technology to remove atmospheric pollutants NO X NO, which accounts for the largest proportion of NO, is effectively converted into harmless substances (such as N 2 ) or a more valuable product (NH 3 NH 2 OH), has broad application prospects.

[0005] MoS 2 MoS is a semiconductor material that is widely used in the fields of photocatalysis and electrocatalysis. In recent years, researchers have conducted research on electrocatalytic NO reduction to synthesize ammonia, but the problem of high overpotential has not been solved, which has greatly limited the development of MoS 2 catalytic activity.

[0006] Therefore, it is urgent to develop a new type of MoS with high catalytic activity. 2 Based on photoelectrocatalytic materials, it can be used for the conversion of atmospheric pollutants such as NO. Summary of the invention

[0007] The purpose of the present invention is to overcome the existing MoS 2 A metal single atom doped MoS is provided to improve the photoelectrocatalytic activity 2 Composite materials and their preparation methods and applications.

[0008] The purpose of the present invention can be achieved by the following technical solutions:

[0009] A metal single atom doped MoS 2 The method for preparing the composite material comprises the following steps:

[0010] The metal nanowires are dispersed in water, and then molybdenum salt and thiourea are added to disperse them evenly to obtain a precursor solution; the precursor solution is subjected to a high-pressure microwave reaction, and the metal nanowires are dissolved to obtain the metal single atom-doped MoS 2 Composite materials.

[0011] Furthermore, the molar ratio of the metal nanowires, molybdenum salt and thiourea is 1:(2-3):(6-9).

[0012] Furthermore, the concentration of the metal nanowires in water is 0.05-0.15 mol / L.

[0013] Furthermore, the metal nanowires include one or more of copper nanowires, silver nanowires, and iron nanowires, preferably copper nanowires.

[0014] Furthermore, the molybdenum salt includes one or more of sodium molybdate and ammonium molybdate, preferably sodium molybdate.

[0015] Furthermore, the high pressure microwave reaction is heated to 150-200° C. at a heating rate of 10-20° C. / min.

[0016] Furthermore, the reaction temperature is preferably 180° C., and the heating rate is preferably 15° C. / min.

[0017] Furthermore, the high pressure microwave reaction time is 10-60 min, preferably 20 min.

[0018] Furthermore, the pressure of the high-pressure microwave reaction is 30-40 bar, preferably 35 bar.

[0019] The present invention also provides a metal single atom doped MoS prepared by the above preparation method. 2 A composite material comprising molybdenum disulfide and metal single atoms supported on the molybdenum disulfide.

[0020] Furthermore, the molybdenum disulfide grows according to the metal nanowire template to form a rod-like structure.

[0021] Furthermore, the metal single atoms are uniformly dispersed on the surface of molybdenum disulfide after the metal nanowires are dissolved.

[0022] Furthermore, the metal single atom is loaded on the (001) crystal plane of the molybdenum disulfide nanorod in a three-coordinate structure.

[0023] The present invention also provides a metal single atom doped MoS 2 Application of composite materials in photoelectrocatalytic reduction of NO to synthesize ammonia.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The present invention prepares a metal single atom doped MoS 2 Composite materials, the addition of metal single atoms to MoS 2 Semiconductor catalysts provide new reaction sites and enhanced conductivity, thereby improving the performance of MoS 2 The photoelectrocatalytic activity of the composite material can be used to achieve efficient NO reduction to synthesize ammonia via photoelectrocatalysis.

[0026] (2) The present invention is used to prepare MoS doped with metal single atoms 2 In the process of composite materials, metal nanowires are used as growth templates, MoS 2 It can grow into a rod-like structure according to the template, thereby increasing the specific surface area of ​​the catalyst and improving the reaction activity.

[0027] (3) MoS of the present invention 2 The composite material is a mixed phase, in which the 1T phase is a conductive phase that provides a good reaction substrate, and the 2H phase is a semiconductor phase that is a photoelectric synergistic matrix that provides photogenerated electrons to participate in the reduction reaction. The Cu single atoms evenly dispersed in the material provide reaction sites that stably bind to NO molecules, and efficiently photocatalytically reduce NO to NH 3 .

[0028] (4) The photogenerated electrons generated by the 2H phase structure of the present invention under illumination are continuously supplied at a relatively low voltage for efficient photoelectric synergistic catalytic reduction of NO to NH 3 .

[0029] (5) The present invention adopts a microwave method to prepare nanocomposite materials, which has the advantages of short reaction time, uniform and controllable reaction temperature and pressure, high efficiency and energy saving, and green environmental protection, and has the application prospect of large-scale preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The metal single atom doped MoS of Example 1 of the present invention 2 Scanning electron micrograph of the composite material.

[0031] Figure 2 The composite material of Example 1 of the present invention and the MoS of Comparative Example 1 2 Transmission electron microscopy image of .

[0032] Figure 3 The metal single atom doped MoS of Example 1 of the present invention 2 X-ray diffraction patterns of the composite materials.

[0033] Figure 4 These are the normalized X-ray absorption near-edge structure (XANES) spectrum and extended X-ray absorption fine structure (EXAFS) spectrum of the Cu-K absorption edge of the composite material of Example 1 of the present invention.

[0034] Figure 5 These are the synchrotron radiation fitting results and DFT results of the composite material of Example 1 of the present invention.

[0035] Figure 6 The composite material of Example 1 of the present invention and the MoS of Comparative Example 1 2 Linear voltammetric scan curves under light and dark conditions in argon and NO-saturated electrolytes, respectively.

[0036] Figure 7 For the photoelectrocatalytic performance test of NH 3 and N 2 H 4 The standard curve of

[0037] Figure 8 The NH ions of the composite material of Example 1 and Comparative Example 1 and Comparative Example 2 under the conditions of photoelectrocatalysis and pure electrocatalysis, respectively. 3 Yield and Faradaic efficiency.

[0038] Fig. 9 NH is the composite material of Example 1 of the present invention under different potentials and catalytic conditions. 3 Yield and Faradaic efficiency. DETAILED DESCRIPTION

[0039] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0040] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0041] In the following examples, metal single atom-doped MoS 2The microwave reactor of the composite material is the Ultra Wave reactor produced by Milestone; the transmission electron microscope characterization uses the Japanese JEM-2100 transmission electron microscope; the XRD characterization of the composite material uses a BRUKER D8 ADVANCE X-ray diffractometer; the electrochemical workstation used in the photoelectrocatalytic NO reduction test is Chenhua CHI 760.

[0042] In the following examples, the preparation process of copper nanowires is as follows:

[0043] Dissolve 500 g of NaOH in 833 mL of deionized water, and slowly add 41.5 mL of 0.1 M Cu(NO 3 ) 2 The aqueous solution was stirred for 40 minutes, 6.225 mL of ethylenediamine and 1.037 mL of 35% hydrazine hydrate aqueous solution were added, and the mixed solution was transferred to an oven at 80°C and stored for 3 hours to obtain Cu NWs.

[0044] Embodiment 1:

[0045] 2 mmol of copper nanowires were ultrasonically dispersed in 20 ml of deionized water, and then 5 mmol of sodium molybdate and 15 mmol of thiourea were added and ultrasonically dispersed. The uniformly mixed liquid of the above substances was placed in a microwave tube to obtain a precursor solution. The microwave tube was then placed in a microwave reactor and the heating rate was set to 15 °C min -1 , the initial pressure was 35 bar, the reaction temperature was 180 °C, and the reaction time was 20 min. After the microwave reaction, the material was collected by centrifugation, washed with deionized water and ethanol three times, and then collected in a vacuum oven at 80 °C overnight to obtain solid powder, thus obtaining Cu single atom-doped MoS 2 Nanocomposite material, denoted as CuSA@MoS 2 .

[0046] Embodiment 2:

[0047] 2 mmol of copper nanowires were ultrasonically dispersed in 20 ml of deionized water, and then 5 mmol of sodium molybdate and 15 mmol of thiourea were added and ultrasonically dispersed. The uniformly mixed liquid of the above substances was placed in a microwave tube to obtain a precursor solution. The microwave tube was then placed in a microwave reactor and the heating rate was set to 15 °C min -1 , the initial pressure was 35 bar, the reaction temperature was 180 °C, and the reaction time was 10 min. After the microwave reaction, the material was collected by centrifugation, washed with deionized water and ethanol three times, and then collected in a vacuum oven at 80 °C overnight to collect solid powder, and finally MoS doped with Cu single atoms was obtained. 2 Nanocomposite materials.

[0048] Embodiment 3:

[0049] 2 mmol of copper nanowires were ultrasonically dispersed in 20 ml of deionized water, and then 5 mmol of sodium molybdate and 15 mmol of thiourea were added and ultrasonically dispersed. The uniformly mixed liquid of the above substances was placed in a microwave tube to obtain a precursor solution. The microwave tube was then placed in a microwave reactor and the heating rate was set to 15 °C min -1 , the initial pressure was 35 bar, the reaction temperature was 180 °C, and the reaction time was 30 min. After the microwave reaction, the material was collected by centrifugation, washed with deionized water and ethanol three times, and then collected in a vacuum oven at 80 °C overnight to collect solid powder, and finally MoS doped with Cu single atoms was obtained. 2 Nanocomposite materials.

[0050] Embodiment 4:

[0051] 2 mmol of copper nanowires were ultrasonically dispersed in 20 ml of deionized water, and then 5 mmol of sodium molybdate and 15 mmol of thiourea were added and ultrasonically dispersed. The uniformly mixed liquid of the above substances was placed in a microwave tube to obtain a precursor solution. The microwave tube was then placed in a microwave reactor and the heating rate was set to 15 °C min -1 , the initial pressure was 35 bar, the reaction temperature was 160 ° C, and the reaction time was 20 min. After the microwave reaction, the material was collected by centrifugation, washed with deionized water and ethanol three times, and then collected in a vacuum oven at 80 ° C overnight to collect solid powder, and finally MoS doped with Cu single atoms was obtained. 2 Nanocomposite materials.

[0052] Embodiment 5:

[0053] 2 mmol of copper nanowires were ultrasonically dispersed in 20 ml of deionized water, and then 5 mmol of sodium molybdate and 15 mmol of thiourea were added and ultrasonically dispersed. The uniformly mixed liquid of the above substances was placed in a microwave tube to obtain a precursor solution. The microwave tube was then placed in a microwave reactor and the heating rate was set to 15 °C min -1 , the initial pressure was 35 bar, the reaction temperature was 200 °C, and the reaction time was 20 min. After the microwave reaction, the material was collected by centrifugation, washed with deionized water and ethanol three times, and then collected in a vacuum oven at 80 °C overnight to collect solid powder, and finally MoS doped with Cu single atoms was obtained. 2 Nanocomposite materials.

[0054] Embodiment 6:

[0055] 1 mmol of copper nanowires was ultrasonically dispersed in 20 ml of deionized water, and then 5 mmol of sodium molybdate and 15 mmol of thiourea were added and ultrasonically dispersed. The uniformly mixed liquid of the above substances was placed in a microwave tube to obtain a precursor solution. The microwave tube was then placed in a microwave reactor and the heating rate was set to 15 °C min -1 , the initial pressure was 35 bar, the reaction temperature was 180 ° C, and the reaction time was 20 min. After the microwave reaction, the material was collected by centrifugation, washed with deionized water and ethanol three times, and then collected in a vacuum oven at 80 ° C overnight to collect solid powder, and finally MoS doped with Cu single atoms was obtained. 2 Nanocomposite materials.

[0056] Embodiment 7:

[0057] 3 mmol of copper nanowires were ultrasonically dispersed in 20 ml of deionized water, and then 5 mmol of sodium molybdate and 15 mmol of thiourea were added and ultrasonically dispersed. The uniformly mixed liquid of the above substances was placed in a microwave tube to obtain a precursor solution. The microwave tube was then placed in a microwave reactor and the heating rate was set to 15 °C min -1 , the initial pressure was 35 bar, the reaction temperature was 180 ° C, and the reaction time was 20 min. After the microwave reaction, the material was collected by centrifugation, washed with deionized water and ethanol three times, and then collected in a vacuum oven at 80 ° C overnight to collect solid powder, and finally MoS doped with Cu single atoms was obtained. 2 Nanocomposite materials.

[0058] Comparative Example 1:

[0059] This comparative example is pure MoS 2 . Add 0.5mmol sodium molybdate and 15mmol thiourea to the solution and disperse it thoroughly by ultrasound for 20 minutes. Transfer the mixed reactants to a quartz container equipped with a microwave system. -1 The product was heated at a heating rate of 1000 °C and an argon pressure of 35 bar for 20 min, cooled to room temperature, and heated with a degasser for 1 h. After cooling to room temperature, the product was thoroughly washed with deionized water and ethanol. The product was thoroughly washed with deionized water and ethanol three times respectively. The black powder was dried at 80 °C in vacuum for 12 h to obtain pure MoS 2 .

[0060] Comparative Example 2:

[0061] This comparative example is pure copper nanowires (CuNWs).

[0062] The present invention performs the following tests on the materials obtained in Example 1 and Comparative Examples 1-2:

[0063] (1) Morphological characterization: Scanning electron microscopy and transmission electron microscopy were used to observe the surface morphology and internal morphology.

[0064] (2) Component characterization: The samples prepared in Example 1 and Comparative Example 1 were characterized by X-ray diffraction patterns, and the composite material of Example 1 was tested by XANES spectrum and EXAFS spectrum.

[0065] (3) Photoelectrocatalytic performance test: The photoelectrocatalytic tests in the present invention were all carried out in an H-type electrolytic cell, with the cathode chamber illuminated through a quartz glass window, the working electrode facing the window, and the test conditions at room temperature and pressure. The electrolyte was 0.5 M Na 2 SO 4 The working electrode was a catalyst-loaded carbon paper, and the reference electrode and counter electrode were Ag / AgCl electrodes and foils (1×1 cm 2 ). 50 mL of electrolyte was added to the reaction chambers on both sides of the electrolytic cell. Before the photoelectrocatalytic reaction, pure Ar was used to purge the cathode chamber to exhaust the remaining air from the reaction cell. The gas flow rate was controlled by a flow meter (30 SCCM). Then, NO / Ar (10 vol.% NO) gas was blown into the cathode reaction cell at 30 SCCM for 30 min before the photoelectrocatalytic reduction reaction began. The gas exhaust was removed using a 4 M saturated KOH solution. NH 3 The Faradaic efficiency and yield were both calculated after 1 h of reaction.

[0066] ①NH 3 Detection:

[0067] Detection of NH using indophenol blue colorimetric assay 3 The presence of NH 3 Quantitative analysis. The coloring agent is 5wt% salicylic acid, 5wt% sodium citrate and 1M NaOH aqueous solution. The above chemicals are mixed evenly to obtain the color developer liquid A. The oxidant liquid B is a 0.05M NaClO aqueous solution. The catalyst is a 1wt% sodium nitroprusside aqueous solution as liquid C. The operation process is to use a pipette to take 100μL of the electrolyte that has been reacted for 1h, and then take 0.5M Na 2 SO 4 The electrolyte is diluted to 2mL, and then 2mL of liquid A, 1mL of liquid B and 200μL of liquid C are added to the liquid to be tested and mixed evenly. The entire color development process needs to be carried out at room temperature and away from light for 2h. After the color development is completed, the light intensity of the color-developed liquid is measured at a wavelength of 665nm using UV-Vis, and the NH 3 concentration.

[0068] ②NH 3The standard curve is as follows: First, prepare 100 ppm NH 4 The Cl solution was used as the mother solution, and the mother solution was subsequently diluted to a series of NH 4 Cl solution, and then developed with indigo blue and detected the absorbance with UV-Vis at a wavelength of 665 nm. The results were plotted with absorbance as the ordinate, and NH 4 + Plot NH concentration on the horizontal axis 3 The standard curve of Figure 7 As shown in a.

[0069] ③N 2 H 4 Detection:

[0070] This article 2 H 4 The detection method of Watt and Chrisp was used. The color developing agent was 15 mL HCl and 2.99 g pC 9 H 11 NO was added to 150 mL of ethanol and stirred evenly. 2 mL of the electrolyte after the reaction was taken out with a pipette, and then 2 mL of the color developer was added to react at room temperature in the dark for 20 min, and then the absorbance was detected by UV-Vis at a wavelength of 455 nm.

[0071] ④N 2 H 4 Standard curve of:

[0072] First, prepare 100ppm N 2 H 4 The mother solution was subsequently diluted to 0.5, 1, 1.5, 2, 2.5, 3, 3.5 ppm of N 2 H 4 The solution was tested for absorbance using the colorimetric method of Watt and Chrisp, and a standard curve was drawn, such as Figure 7 As shown in b.

[0073] Depend on Figure 1-2 It can be seen that in the preparation process of Example 1, copper nanowires were used as templates, and MoS 2 The nanowires grow into rod-shaped nanoflower structures with no obvious metal particles on the surface. In addition, the nanowires are dissolved and doped into molybdenum disulfide during the microwave process, and no copper is observed inside the material. 2 It naturally grows into a spherical nanoflower structure. Pure MoS 2 It is easy to accumulate, and the overall specific surface area of ​​the material is small, while the rod-shaped MoS 2It can increase the reaction specific surface area and facilitate the gas-liquid phase reaction.

[0074] Depend on Figure 3 The X-ray diffraction pattern of and the peak pattern of elemental copper show that the crystal structure of the composite material of Example 1 is mainly molybdenum disulfide, and no peak of elemental copper is observed.

[0075] Depend on Figure 4 From the XANES and EXAFS spectra, we can see that Figure 4 (a) shows the CuSA@MoS of Example 1 2 And Cu foil, Cu 2 Cu k-edge X-ray absorption near-edge structure spectra of O and CuO. CuSA@MoS 2 The absorption edge of Cu 2 O and CuO, indicating that the oxidation state of the copper component is between +1 and +2. In the Fourier transform EXAFS spectrum, CuSA@MoS 2 Nearby There is an obvious strong peak at , which can be attributed to the typical Cu-S coordination. 2 The S atom in the structure is 3-coordinated. No Cu 2 High-resolution wavelet transform EXAFS analysis was performed in k and R space to further confirm the peaks of CuSA@MoS 2 Monodisperse copper atoms in the

[0076] Figure 5 From the synchrotron radiation fitting results and DFT results, it can be seen that the metal single atom is loaded on the (001) crystal plane of MoS2 nanorods in a three-coordinated structure.

[0077] Figure 6 CuSA@MoS of Example 1 2 The LSV curves (linear scanning voltammetry curves) of the catalyst under light and dark conditions in Ar and NO atmospheres respectively show that the LSV curves under light and dark conditions in Ar atmosphere are basically the same, while the current density under light conditions in NO atmosphere is significantly increased. This shows that the CuSA@MoS 2 The loading of Cu single atoms in the catalyst provides uniformly dispersed highly active reaction sites, accelerating the kinetics of NO molecule adsorption and activation.

[0078] Figure 8 It shows that under the conditions of photoelectrocatalysis and pure electrocatalysis, the CuSA@MoS 2 And pure MoS 2 and NH of pure copper nanowires3 Yield and Faraday efficiency, it can be clearly seen that the CuSA@MoS 2 The photoelectrocatalytic activity of NH 3 The yield and Faradaic efficiency are significantly higher than those of pure MoS 2 and pure copper nanowires.

[0079] Depend on Fig. 9 The CuSA@MoS of Example 1 is shown 2 NH of PEC NORR (photoelectrocatalytic NO reduction reaction) at different potentials 3 Yield and Faradaic efficiency of CuSA@MoS at -0.3 V 2 NH 3 The yield was the highest (yield was 60.55 μmol h -1 cm -2 mg -1 , the Faradaic efficiency is 90.66%). At -0.3V pure electrocatalytic NH 3 The yield was 35.61 μmol h -1 cm -2 mg -1 , the Faradaic efficiency is 80.26%, and the enhancement ratios of yield and Faradaic efficiency are 70.03% and 12.96%, respectively, which indicates that there is a synergistic effect of introducing light to assist the electrocatalytic reduction of NO.

[0080] In summary, the present invention uses a convenient and rapid high-pressure microwave reaction to obtain metal single atom-doped MoS 2 The nanorod composite material confirms that the copper in the material exists in a single atomic structure. The composite material is prepared as a semiconductor photocathode and applied to photocatalytic reduction of NO to synthesize ammonia, achieving excellent ammonia yield and Faraday efficiency, thereby proving that the present invention has unique application prospects and value in the field of photocatalytic reduction of NO to synthesize ammonia.

[0081] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a metal single atom doped MoS2 composite material, characterized in that: The following steps are involved: The metal nanowires are dispersed in water, and then molybdenum salt and thiourea are added to uniformly disperse the metal nanowires to obtain a precursor solution; The precursor solution is subjected to high-pressure microwave reaction, and the metal nanowires are dissolved to obtain the metal single atom-doped MoS2 composite material.

2. The method for preparing a metal single atom doped MoS2 composite material according to claim 1, characterized in that: The molar ratio of the metal nanowires, the molybdenum salt and the thiourea is 1:(2-3):(6-9).

3. The method for preparing a metal single atom doped MoS2 composite material according to claim 1, characterized in that: The concentration of the metal nanowires in water is 0.05-0.15 mol / L.

4. The method for preparing a metal single atom doped MoS2 composite material according to claim 1, characterized in that: The metal nanowires include one or more of copper nanowires, silver nanowires, and iron nanowires.

5. The method for preparing a metal single atom doped MoS2 composite material according to claim 1, characterized in that: The molybdenum salt includes one or more of sodium molybdate or ammonium molybdate.

6. The method for preparing a metal single atom doped MoS2 composite material according to claim 1, characterized in that: The high pressure microwave reaction is heated to 150-200° C. at a heating rate of 10-20° C. / min.

7. The method for preparing a metal single atom doped MoS2 composite material according to claim 1, characterized in that: The high pressure microwave reaction time is 10-60 min, and the pressure is 30-40 bar.

8. A metal single atom doped MoS2 composite material obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The composite material comprises molybdenum disulfide and metal single atoms supported on the molybdenum disulfide; The molybdenum disulfide grows according to the metal nanowire template to form a rod-like structure; The metal single atom is a metal nanowire that is evenly dispersed on the surface of molybdenum disulfide after being dissolved.

9. The metal single atom doped MoS2 composite material according to claim 8, characterized in that: The metal single atom is loaded on the (001) crystal plane of the molybdenum disulfide nanorod in a three-coordinate structure.

10. Use of the metal single atom doped MoS2 composite material according to claim 8 in photoelectrocatalytic reduction of NO to synthesize ammonia.